If it's not what You are looking for type in the equation solver your own equation and let us solve it.
23=-2(24-b)+3(b-3)
We simplify the equation to the form, which is simple to understand
23=-2(24-b)+3(b-3)
Reorder the terms in parentheses
23=+(-48+2b)+3*(b-3)
Remove unnecessary parentheses
+23=-48+2b+3+*(+b-3+)
Reorder the terms in parentheses
23=-48+2b+(+3b-9)
Remove unnecessary parentheses
+23=-48+2b+3b-9
We move all terms containing b to the left and all other terms to the right.
-2b-3b=-48-9-23
We simplify left and right side of the equation.
-5b=-80
We divide both sides of the equation by -5 to get b.
b=16
| 15x+21(x-2)=318 | | 4x^2+7-3=0 | | 19x-(4x-9)=84 | | 19x-3(4x-9)=84 | | 5m+10=9m-2 | | 5(6z+1)-9=146 | | 3(4x-1)=36 | | (-6)(9)= | | (4-9)= | | 4w^2=-12w-5 | | [10-2]= | | 12*-72= | | 14y=-84 | | v+-391=1255 | | v+-391=255 | | 8(4+4(5))= | | v+255=-391 | | 8(4+5(5))= | | -5(2x+1)=1-4(x+9) | | (x-5)(2x^2+3x-1)= | | 3(x+9)=42 | | X^6+5x^3-6=0 | | x(x)+5x+6=0 | | x(x)-5x-6=0 | | (3x^2-4x+10)-(x^2-9x+13)= | | c+150=1860 | | 5x(x)=6+2x | | x-13=-3 | | (2x^2-x+7)+(3x^2+x-9)= | | x(x)-7x-8=0 | | (40x)+(20*1.5x)=1625 | | 2-4y=4-5y |